Physical and Gamma Ray Attenuation Properties of Bismuth-Lead-Phosphate Glass - S. Mater , Abo-alqasem; A. Mansouri , Rasha; M. Tawati , Daefalla; A. Ikraiam , Fawzi; A. Hussien , Nagi (Scientific Journal of University of Benghazi, 2024)
In this paper, the physical characteristics and radiation attenuation parameters of five ternary (50-x) PbO-xBi2O3-50P2O5 glass samples with different compositions were examined. The physical properties investigated were glass density (ρ), molar volume (VM), molar volume of oxygen (VO), and oxygen packing density (OPD). An empirical formula was used to determine the glass density theoretically and compared with the experimental density obtained from the Archimedes method. The comparison yielded reasonable results but did not achieve the desired level of accuracy as expected. The findings revealed that both density and molar volume exhibited an increase with higher Bi2O3 content. However, the molar volume of oxygen (VO) and oxygen packing density (OPD) show inconsistent behavior, showing a slight increase in VO and a decrease in OPD. Furthermore, the essential radiation properties, including the coefficient of linear attenuation (LAC), coefficient of mass attenuation (MAC), half-value layer (HVL), and tenth-value layer (TVL), were determined through experimental and theoretical calculations using the NaI (Tl) detection system and the Phy-X/PSD program, respectively. The results indicated reasonable consistency between the two methods, with the Bi16Pb34P50 sample demonstrating superior radiological properties among the samples. Overall, the study illustrated that the addition of bismuth to phosphate and lead glass improved the glass samples' radiation and physical characteristics.